Electrode assembly having insulating film formed on tab, method for manufacturing same, and lithium secondary battery comprising same

By forming an organic-inorganic hybrid composition insulating film of inorganic particles and binder polymer on the electrode joint of the lithium secondary battery, the increase in resistance and fire/explosion risks caused by the short circuit of the electrode joint is solved, and the safety of the battery and the improvement of defect rate in the production process is achieved.

CN119864613APending Publication Date: 2025-04-22LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510062265.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-02-27
Filing Date
2021-01-29
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing lithium secondary batteries are prone to short circuits at electrode joints, resulting in increased resistance, reduced capacity and fire/explosion risks. The existing insulation technology has shortcomings in improving battery safety and reducing defect rates.

Method used

An insulating film of an organic-inorganic hybrid composition including inorganic particles and a binder polymer is formed on the joint of the electrode to prevent a short circuit between the positive electrode and the negative electrode, and an insulating film is formed on the surface of the electrode joint by lamination or transfer techniques during the manufacturing process.

Benefits of technology

It effectively prevents short circuits between electrodes, reduces the reduction of resistance and capacity, improves the safety of the battery and the defect rate during production, and avoids the risk of fire/explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864613A_ABST
    Figure CN119864613A_ABST
Patent Text Reader

Abstract

An electrode assembly in which an insulating film is formed on a tab, a method for manufacturing the same, and a lithium secondary battery including the same. The present invention relates to an electrode assembly, a method for manufacturing the same, and a lithium secondary battery comprising the same, the electrode assembly comprising an electrode, a separator, and a counter electrode for a lithium secondary battery, an electrode active material layer is formed on an electrode current collector including an electrode current collector substrate and a tab extending from the electrode current collector substrate, the tab having an insulating film formed on part or all of at least one surface thereof, and the insulating film being an organic-inorganic composite film including inorganic particles and a binder polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with the original application number 202180004618.3 (International application number: PCT / KR2021 / 001228, application date: January 29, 2021, invention name: Electrode assembly with an insulating film formed on the joint, its manufacturing method and lithium secondary battery containing the same). Technical Field

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to and the benefit of Korean Patent Application No. 10-2020-0024624 filed on February 27, 2020, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0004] The present invention relates to an electrode assembly having an insulating film formed on a joint, a manufacturing method thereof, and a lithium secondary battery comprising the electrode assembly. Background Art

[0005] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative or clean energy, and as a part of this, the field that has been most actively researched is the field of power generation and condensation using electrochemistry.

[0006] Currently, a representative example of an electrochemical device using such electrochemical energy may be a secondary battery, and its application fields are gradually expanding.

[0007] Recently, with the technological development and increase in demand for portable devices such as portable computers, portable phones, cameras, etc., the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, a large number of studies have been conducted on environmentally friendly lithium secondary batteries representing high charge and discharge characteristics and life characteristics, and lithium secondary batteries have been commercialized and widely used.

[0008] The electrode assembly embedded in the battery case is a power generation device consisting of a stacked structure of positive electrode / separator / negative electrode and is rechargeable and dischargeable. The electrode assembly is classified into a jelly roll type in which a long sheet-type separator coated with active material is wound between the positive electrode and the negative electrode, and a stacked type in which a plurality of small-sized positive and negative electrodes are stacked in sequence with a separator between them. As a combination thereof, the electrode assembly is classified into a stacking / folding type, in which a double cell or a full cell including a positive electrode, a negative electrode and a separator is wound with a long sheet-like separator having a long full cell, and in the stacking / folding type, the double cell or the full cell is laminated and then stacked.

[0009] In addition, generally, a lithium secondary battery has a structure in which a non-aqueous electrolyte expands in an electrode assembly including a positive electrode, a negative electrode and a porous separator. The positive electrode is prepared by coating a positive electrode mixture containing a positive electrode active material on an aluminum foil, and the negative electrode is prepared by coating a negative electrode mixture containing a negative electrode active material on a copper foil.

[0010] Generally, the positive electrode active material is a lithium displacement metal oxide, and the negative electrode active material uses a carbon material. However, recently, as a negative electrode active material, lithium metal batteries using lithium metal itself have been commercialized, and in addition, research on lithium-free batteries has been actively conducted, in which only a current collector is used as a negative electrode during the manufacturing process, lithium is received from the positive electrode by discharge, and lithium metal is used as a negative electrode active material.

[0011] In addition, in such lithium secondary batteries, the positive electrode and the negative electrode are formed with different areas due to differences in capacity, etc. For this reason, the edge portion of the side formed larger and the joint of the side formed smaller frequently contact each other to cause a short circuit. In some cases, when the active material is applied to the joint, even if a large current flows in a short time due to a short circuit, etc., there is a risk of fire / explosion because the battery generates heat through heat generation.

[0012] In order to solve this phenomenon, a technique of attaching a polymer insulating tape to an electrode tab or for coating an insulating layer has been applied to mass production.

[0013] However, in this case, when the insulating tape or insulating layer is formed on the electrode active material layer, the resistance increases and the defect rate increases. In particular, when the insulating layer is coated on the electrode active material layer during the coating process, the resistance increases rapidly while filling the pores of the electrode active material layer, and the cell capacity decreases, resulting in the problem that these cells are often classified as defective cells.

[0014] Therefore, since resistance increase and capacity reduction are effectively prevented by solving the above-mentioned problems, a structure capable of ensuring battery safety while reducing a defect rate according to battery production is highly desired. Summary of the invention

[0015] Technical issues

[0016] Therefore, an object of the present invention is to solve the above-mentioned problems in the related art as well as the technical problems demanded in the past.

[0017] Specifically, the present invention is directed to providing an electrode assembly, a method for manufacturing the same, and a lithium secondary battery comprising the electrode assembly by forming an organic-inorganic hybrid composition including inorganic particles and a binder polymer in the form of an insulating film on a joint of an electrode, so as to effectively prevent a short circuit that may occur between a positive electrode and a negative electrode while preventing an increase in defect rate due to increased resistance and reduced capacity.

[0018] Technical Solution

[0019] Therefore, an exemplary embodiment of the present invention provides an electrode assembly for a lithium secondary battery, the electrode assembly comprising: an electrode, a separator and a counter electrode, wherein the electrode has the following structure: wherein an electrode active material layer is formed on an electrode current collector, the electrode current collector comprises an electrode current collector substrate and a joint extending from the electrode current collector substrate, an insulating film is formed on some or all of at least one surface of the joint, and the insulating film is an organic-inorganic hybrid film comprising inorganic particles and a binder polymer.

[0020] Specifically, the insulating film may be formed on the joint of the electrodes in a direction in which the electrode and the counter electrode face each other.

[0021] Furthermore, an insulating film may be formed on a joint of the opposite electrode in a direction in which the electrode and the opposite electrode face each other.

[0022] More specifically, an insulating film is formed on the entire both sides of the joint to prevent a short circuit regardless of any direction or any position.

[0023] In addition, the binder polymer constituting the organic-inorganic hybrid membrane can be at least one selected from the group consisting of: polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose and polyvinyl alcohol.

[0024] The inorganic particles may be at least one selected from the group consisting of (a) inorganic particles having a dielectric constant of 1 or more, (b) inorganic particles having piezoelectricity, (c) thermally conductive inorganic particles, and (d) inorganic particles having lithium ion transporting capability.

[0025] At this time, the content of the inorganic particles may be 1 to 99 weight percent per 100 weight percent of the mixture of the inorganic particles and the binder polymer.

[0026] The insulating film may be formed with a thickness of 0.1 μm to 100 μm.

[0027] In one example, an electrode may be a positive electrode and an opposing electrode may be a negative electrode, and in another example, an electrode may be a negative electrode and an opposing electrode may be a positive electrode.

[0028] The diaphragm may be an SRS diaphragm.

[0029] Another exemplary embodiment of the present invention provides a method for manufacturing an electrode assembly, the method comprising the following steps:

[0030] (a) preparing an electrode and a counter electrode, wherein the electrode has the following structure: an electrode active material layer is formed on an electrode current collector, the electrode current collector comprising an electrode current collecting substrate and a tab extending from the electrode current collecting substrate;

[0031] (b) preparing a laminate by coating an organic-inorganic hybrid composition including inorganic particles and a binder polymer on a release film and drying the composition to thereby laminate an organic-inorganic hybrid film on the release film;

[0032] (c) forming an insulating film on a part or the whole of at least one surface of the joint of the electrode by laminating an organic-inorganic hybrid film after removing a release film from the laminate or directly transferring the organic-inorganic hybrid film from the laminate; and

[0033] (d) An electrode assembly is manufactured with the separator interposed between an electrode in which the insulating film is formed on at least one surface of a joint and an opposite electrode.

[0034] At this time, as described above, the insulating film may be formed on the joint of the electrode in the direction in which the electrode and the opposite electrode face each other, and may be further formed on the joint of the opposite electrode in the direction in which the electrode and the opposite electrode face each other.

[0035] Yet another exemplary embodiment of the present invention provides a lithium secondary battery including an electrode assembly and an electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is an exploded perspective view of an electrode, a separator, and a counter electrode according to an exemplary embodiment of the present invention. DETAILED DESCRIPTION

[0037] Therefore, an exemplary embodiment of the present invention provides an electrode assembly for a lithium secondary battery, the electrode assembly including:

[0038] electrodes, separators and counter electrodes,

[0039] The electrode has the following structure: an electrode active material layer is formed on an electrode current collector, the electrode current collector includes an electrode current collecting substrate and a joint extending from the electrode current collecting substrate,

[0040] An insulating film is formed on some or all of at least one surface of the joint, and the insulating film is an organic-inorganic hybrid film including inorganic particles and a binder polymer.

[0041] At this time, specifically, the insulating film may be formed on the joint of the electrodes in a direction in which the electrode and the counter electrode face each other.

[0042] Furthermore, an insulating film may be formed on a joint of the opposite electrode in a direction in which the electrode and the opposite electrode face each other.

[0043] Therefore, as one example, when the opposite electrode is laminated on both sides of the electrode, the insulating film may be formed on both sides of the joint of the electrode, or may be included in directions facing the electrode and the opposite electrode, respectively.

[0044] As another example, when an electrode and an opposite electrode are included one by one, an insulating film of the electrode is formed on one side or both sides facing the opposite electrode, and the opposite electrode may or may not include the insulating film.

[0045] However, when two or more electrodes and two or more counter electrodes are included, more various structures can be realized.

[0046] For example, when all two or more electrodes include an insulating film only on one side of a joint, an insulating film may be included on one or both sides of the joint of one or more opposite electrodes, so that the insulating film may be formed on the joint between the opposite electrode and the electrode on the other side of the electrode.

[0047] On the other hand, if two or more electrodes include insulating films on both sides of the joint, the opposite electrode may or may not include an insulating film on the joint.

[0048] In addition, when some of two or more electrodes include an insulating film only on one side of the joint and some of two or more electrodes include an insulating film on both sides of the joint, various structures can be realized at a position where there is no insulating film between the electrode and the opposite electrode, such as, the insulating film can be included on one side or both sides of the joint of the opposite electrode.

[0049] That is, any structure in which an insulating film can be formed on one or both sides of a joint of an electrode and / or an opposite electrode at a location where a short circuit may occur between the electrode and the opposite electrode is included in the scope of the present invention.

[0050] More specifically, an insulating film is formed on the entire both sides of the joint to effectively prevent a short circuit in any direction or at any position while simplifying the manufacturing process.

[0051] In addition, since the insulating film according to the present invention can be formed throughout the joint and may affect the electrode active material layer during the formation of the insulating film, the insulating film should not interfere with the movement of lithium ions according to the charge and discharge of the electrode, thereby preventing the secondary battery performance from deteriorating.

[0052] Therefore, the insulating film may be an organic-inorganic hybrid film including inorganic particles and a binder polymer to ensure the mobility of lithium ions. This organic-inorganic hybrid film has better lithium ion mobility than the separator, and even if the organic-inorganic hybrid film affects the electrode active material layer, the organic-inorganic hybrid film can prevent the reduction of the capacity and output performance of the battery.

[0053] The binder polymer is not limited as long as it does not cause a side reaction with the electrolyte, but in particular, the glass transition temperature (Tg) may be used as low as possible, preferably in the range of -200° C. to -200° C. This is because the mechanical properties of the final insulating film can be improved.

[0054] In addition, the binder polymer does not necessarily have ion conductivity, but it is more preferable to use a polymer having ion conductivity. When the insulating film covers a part of the electrode, it is preferable in terms of capacity because lithium ions of the active material are movable even in that part.

[0055] Therefore, it is preferred that the binder polymer has a dielectric constant as high as possible. In fact, since the decomposition rate of the salt in the electrolyte depends on the dielectric constant of the electrolyte solvent, the dielectric constant of the polymer increases, and the decomposition rate of the salt in the electrolyte can be increased more. The dielectric constant of the polymer is 1 or higher, and specifically can be used in the range of 1.0 to 100 (measurement frequency = 1kHz), and is particularly preferably 10 or higher.

[0056] In addition to the above functions, the binder polymer gels during swelling in the liquid electrolyte to have a property capable of exhibiting a high electrolyte swelling degree. In fact, when the binder polymer is a polymer having an excellent electrolyte swelling degree, the electrolyte injected after assembling the battery penetrates into the polymer and the polymer containing the absorbed electrolyte has electrolyte ion conductivity. Therefore, if possible, in the polymer, the solubility index is preferably 15 to 45 MPa 1 / 2 , more preferably, between 15 and 25 MPa 1 / 2 and 30 to 45 MPa 1 / 2 When the solubility index is less than 15MPa 1 / 2 and greater than 45MPa 1 / 2 The battery's normal liquid electrolyte is difficult to expand when heated.

[0057] Examples of binder polymers may include polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose and polyvinyl alcohol, or mixtures thereof, but are not limited thereto. Any material including the above-mentioned properties may be used alone or in combination.

[0058] In addition, as another component constituting the insulating film, the inorganic particles form micropores by forming gaps between the inorganic particles and serve as a spacer capable of maintaining a physical form. In addition, since the inorganic particles generally have the characteristic that the physical properties do not change even at a high temperature of 200°C or higher, the formed organic-inorganic hybrid layer has excellent heat resistance.

[0059] The inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are not particularly limited as long as they are within the operating voltage range of the battery to be applied (for example, based on Li / Li + In particular, when inorganic particles having ion migration ability are used, since the performance can be improved by increasing the ionic conductivity in the electrochemical device, it is preferred to increase the ionic conductivity as high as possible. In addition, when the inorganic particles have a high density, they are difficult to disperse during the manufacturing process, and there is a problem of weight increase when manufacturing the battery, so it is preferred to make the density as small as possible. In addition, inorganic materials with high dielectric constants help to increase the decomposition rate of electrolyte salts (e.g., lithium salts in liquid electrolytes) to improve the ionic conductivity of the electrolyte. Finally, more preferably, the inorganic particles with thermal conductivity have excellent heat absorption to prevent the phenomenon of thermal explosion caused by local concentration of heat to form heating points.

[0060] For the above reasons, the inorganic particles are preferably at least one selected from the group consisting of: (a) high dielectric inorganic particles having a dielectric constant of 1 or higher, 5 or higher, preferably 10 or higher, (b) inorganic particles having piezoelectricity, (c) thermally conductive inorganic particles, and (d) inorganic particles having lithium ion migration ability.

[0061] Inorganic particles with piezoelectricity refer to materials that are non-conductive under atmospheric pressure but have conductive properties through internal structural changes when a predetermined pressure is applied. Inorganic particles with piezoelectricity refer to the following materials: the material exhibits high dielectric characteristics with a dielectric constant of 100 or higher, and has the function of generating a potential difference between two sides when one side is charged positively and the other side is charged negatively by the charges generated when tensioned or compressed by applying a predetermined pressure.

[0062] When using inorganic particles with the above characteristics as a component of an insulating film, the inorganic particles can not only prevent direct contact between two electrodes caused by external impact or dendrite growth, but also prevent the generation of a potential difference in the particles due to the piezoelectricity of the inorganic particles caused by external impact, thereby enabling electron movement, that is, a minute current flows between the two electrodes, thereby gently reducing the battery voltage and promoting an improvement in safety.

[0063] Examples of inorganic particles with piezoelectricity include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT), PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (H f O2) or mixtures thereof, but are not limited thereto.

[0064] Inorganic particles with lithium ion migration ability refer to inorganic particles that contain lithium element but have the function of moving lithium ions without storing lithium. Since inorganic particles with lithium ion migration ability may migrate and move lithium ions due to a kind of defect existing in the particle structure, it is possible to prevent the reduction of lithium migration rate due to the formation of an insulating film and prevent the reduction of battery capacity.

[0065] Examples of inorganic particles with lithium ion migration ability include (LiAlTiP) x O y -type glass (0 < x < 4, 0 < y < 13) (such as lithium phosphate (Li3PO4)), lithium titanium phosphate (Li x Ti y PO 43 , 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z PO 43 , 0 < x < 2, 0 < y < 1, 0 < z < 3)), and 14Li2O-9Al2O3-38TiO2-39P2O5, SiS2-type glass (Li x Siy S z such that 0 < x < 3, 0 < y < 2, 0 < z < 4) (such as lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3)), lithium germanium thiophosphate (Li x Ge y P z S w such that 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5) (such as Li 3.25 Ge 0.25 P 0.75 S4) and lithium nitride (Li x N y such that 0 < x < 4, 0 < y < 2) (such as Li3N) and P2S5-based glasses (Li x P y S z such that 0 < x < 3, 0 < y < 3, 0 < z < 7) (such as LiI-Li2S-P2S5) or mixtures thereof, but not limited thereto.

[0066] In addition, examples of inorganic particles having a dielectric constant of 1 or higher include SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, or mixtures thereof, but not limited thereto.

[0067] Thermally conductive inorganic particles are materials having insulating properties that provide low thermal resistance but do not provide electrical conductivity. For example, the thermally conductive inorganic particles may be at least one selected from the group consisting of aluminum nitride (AlN), boron nitride (BN), aluminum oxide (Al2O3), silicon carbide (SiC), and beryllium oxide (BeO), but not limited thereto.

[0068] When high dielectric inorganic particles, inorganic particles having piezoelectricity, thermally conductive inorganic particles, and inorganic particles having lithium ion migration ability are combined, their synergistic effects can be doubled.

[0069] The size of the inorganic particles is not limited, but is preferably in the range of 0.001 μm to 10 μm to form an insulating film with a uniform thickness and ensure an appropriate porosity between the inorganic particles. If the size is less than 0.001 μm, the dispersibility decreases, and it is difficult to adjust the physical properties when manufacturing an organic-inorganic hybrid film; when the size is greater than 10 μm, the thickness increases, the mechanical properties decrease, and due to the too large pore size, the function of the insulating film cannot be fully exerted, and the probability of internal short circuit increases during battery charging and discharging.

[0070] The content of the inorganic particles is not particularly limited, but is preferably 1 to 99 weight percent of the mixture of the inorganic particles and the binder polymer per 100 weight percent, and more preferably 10 to 95 weight percent. When the content is less than 1 weight percent, because the content of the polymer is too high, the pore size is reduced and the porosity is reduced due to the reduction of the gaps formed between the inorganic particles, and the mobility of the lithium ions may be reduced. In contrast, when the content exceeds 99 weight percent, because the polymer content is too low, the mechanical properties of the final insulating film are also reduced due to the reduced adhesion between the inorganic particles.

[0071] Therefore, when the insulating film of the present invention is formed by an organic-inorganic hybrid film mixed with a binder polymer and inorganic particles, the insulating film has a uniform pore structure formed by the interstitial volume between the inorganic particles. Since lithium ions move smoothly through these pores and a large amount of electrolyte is filled to show a high degree of expansion, it is possible to prevent the battery performance from being deteriorated due to the formation of the insulating film.

[0072] At this time, the pore size and porosity can be adjusted together by adjusting the size and content of the inorganic particles.

[0073] In addition, in the organic-inorganic hybrid film composed of inorganic particles and a binder polymer, high-temperature thermal shrinkage does not occur due to the heat resistance of the inorganic particles. Therefore, since the insulating film can be maintained even under excessive conditions caused by internal or external factors such as high temperature, overcharge, external impact, etc., short circuits can be effectively prevented, and thermal explosion can also be delayed due to the endothermic effect of the inorganic particles.

[0074] Such an insulating film may be formed to a thickness of, for example, 0.1 μm to 100 μm, specifically, 1 μm or more, 2 μm or more, or 3 μm or more, and may be 50 μm or less, 30 μm or less, or 20 μm or less.

[0075] Outside the above range, if the thickness of the insulating film is too thin, the effect of preventing short circuit may not be obtained, and if the thickness is too thick, the mobility of lithium ions decreases, and because the insulating film may affect welding with the electrode terminal, it is not preferred.

[0076] On the other hand, after repeated in-depth studies by the applicant of the present invention, when the insulator formed on the joint according to the present invention is in the form of an insulating film, it exhibits optimal safety and does not cause degradation of secondary battery characteristics such as increased resistance, reduced capacity, and reduced ion conductivity. In contrast, when the organic-inorganic hybrid composition is directly coated on the joint, this organic-inorganic hybrid composition can be coated on the electrode active material layer. At this time, it is found that the following is not preferred: while filling the pores of the electrode active material layer, the resistance increases and the capacity decreases, and as a result, the performance of the secondary battery deteriorates.

[0077] Therefore, in order to exclude the form to be coated herein, it is referred to as an insulating film rather than an insulating layer.

[0078] The insulating film is an insulating film prepared separately, and may be laminated or transferred and formed on the electrode. Therefore, in the present invention, the "formation" of the insulating film is a concept including "lamination" and "transfer".

[0079] An example of a structure according to the invention is more clearly seen in Figure 1 Shown in.

[0080] Figure 1 An exploded perspective view of an electrode assembly according to an exemplary embodiment of the present invention is shown, in which an insulating film is formed on one side of an electrode tap.

[0081] Reference Figure 1 , the electrode assembly includes an electrode 100, an opposite electrode 120, and a separator 110, and the electrode 100 and the opposite electrode 120 include joints 101 and 121, respectively.

[0082] Here, the insulating film 130 is formed on the entire one side of the joint 101 in a direction in which the electrode 100 faces the opposite electrode 120 .

[0083] In addition, in the present invention, the electrode may be a positive electrode or a negative electrode.

[0084] For example, when an electrode is a positive electrode, the opposite electrode may be a negative electrode, and when an electrode is a negative electrode, the opposite electrode may be a positive electrode.

[0085] When the electrode is a positive electrode or a negative electrode, the electrode may be formed into a structure in which an electrode slurry including an electrode active material, a conductive material, and a binder is coated, dried, and rolled on at least one side of an electrode current collector to form an electrode active material layer. Similarly, the opposite electrode may be formed into a structure in which an electrode slurry including an electrode active material, a conductive material, and a binder is coated, dried, and rolled on at least one side of an electrode current collector to form an electrode active material layer.

[0086] Alternatively, when the electrode according to the present invention is a positive electrode, the electrode can be formed into a structure in which an electrode slurry including an electrode active material, a conductive material and a binder is coated, dried and rolled on at least one side of an electrode current collector to form an electrode active material layer. The opposite electrode, the negative electrode, can be formed into a structure in which lithium metal is deposited and coated on an electrode current collector, or can also be formed only by an electrode current collector.

[0087] Alternatively, when the electrode according to the present invention is a negative electrode, the electrode can be formed into a structure in which lithium metal is deposited and coated on an electrode current collector, or can also be formed only by an electrode current collector. The opposite electrode, the positive electrode, can be formed into a structure in which an electrode slurry including an electrode active material, a conductive material and a binder is coated, dried and rolled on at least one side of an electrode current collector to form an electrode active material layer.

[0088] That is, according to the electrode assembly of the present invention, lithium ion batteries, lithium polymer batteries, etc. can be manufactured, and lithium metal batteries using lithium metal as negative electrode active materials, lithium-free batteries composed only of negative electrode active materials, etc. can also be manufactured.

[0089] In addition, the electrode active material contained in the positive electrode refers to the positive electrode active material, and the electrode current collector refers to the positive electrode current collector.

[0090] The positive electrode current collector is not particularly limited as long as it is generally prepared with a thickness of 3 to 500 μm and has high conductivity without causing chemical changes in the corresponding battery. For example, the positive electrode current collector can use one material selected from the following materials: stainless steel, aluminum, nickel, titanium, and aluminum or stainless steel treated with carbon, nickel, titanium or silver on the surface, and aluminum can be used in particular. The current collector can increase the adhesion of the positive electrode active material by forming fine irregularities on its surface, and can have various forms, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0091] The positive electrode active material may be composed of, for example, a layered compound such as lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium manganese oxide (such as Li 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2); lithium copper oxide (Li2CuO2); vanadium oxides (such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7); 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, x = 0.01 to 0.3); represented by the chemical formula LiMn 2-x Mx Lithium manganese composite oxides represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4, in which some Li in the chemical formula is replaced by alkaline earth metal ions; disulfides; Fe2(MoO4)3, etc., but not limited thereto.

[0092] Similarly, the electrode active material contained in the negative electrode is called the negative electrode active material, and the electrode current collector is called the negative electrode current collector.

[0093] The negative electrode current collector is usually prepared with a thickness of 3 to 50 μm. If such a negative electrode current collector has conductivity and does not cause chemical changes in the corresponding battery, such a negative electrode current collector is not particularly limited. For example, the following materials can be used for the negative electrode current collector: copper, stainless steel, aluminum, nickel, titanium, carbon-plastic, carbon, nickel, titanium or silver-treated copper or stainless steel, and in particular, aluminum-cadmium alloys, etc. can be used. In addition, like the positive electrode current collector, fine irregularities are formed on its surface to increase the adhesion of the negative electrode active material, and the negative electrode current collector can have various forms, such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabrics, etc.

[0094] In addition, in a lithium metal battery, a negative electrode current collector can be prepared such that lithium metal itself can be used as the current collector and the active material, and lithium metal can be used as the current collector.

[0095] The negative electrode active material can use, for example, carbon (such as graphite carbon, graphite-like carbon, etc.); metal composite oxides (such as Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2, 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8)); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides (such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5); conductive polymers (such as polyacetylene; Li-Co-Ni-based materials, etc.).

[0096] Based on the total weight of the mixture including the positive electrode active material, the conductive material is generally added at 0.1 to 30 weight percent, specifically at 1 to 10 weight percent, and more specifically at 1 to 5 weight percent. This conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the corresponding battery. Conductive materials can be used, for example: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, funnel black, lamp black, summer black; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorinated carbon, aluminum, nickel powder; conductive whiskeys, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, carbon nanotubes (CNTs), etc.

[0097] The binder is a component that supports the binding of the active material to the conductive material and to the current collector, and is generally added at 0.1 to 30 weight percent, specifically 1 to 10 weight percent, and more specifically 1 to 5 weight percent based on the total weight of the mixture containing the positive electrode active material. Examples of binders may include polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-dipolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various airborne polymers, and the like.

[0098] In addition, the separator is inserted between the positive electrode and the negative electrode, and an insulating film with high ion permeability and mechanical strength can be used. The pore size of the separator is generally 0.01 μm to 10 μm, and its thickness is generally 1 μm to 300 μm. As such a separator, for example, a sheet, a non-woven fabric, etc. composed of an olefin polymer such as chemically resistant and hydrophilic polypropylene; glass fiber, polyethylene, etc. As an electrolyte, when a solid electrolyte (such as a polymer) is used, the solid electrolyte can also be used as a separator.

[0099] Specifically, the separator may be a safety reinforced separator (SRS). The SRS separator has a structure in which an organic / inorganic composite porous coating is coated on a polyolefin-based separator substrate.

[0100] The inorganic particles and the binder polymer constituting the organic / inorganic composite porous coating layer of the SRS separator are similar to those described above, and the contents disclosed in the applicant's application No. 10-2009-0018123 are incorporated by reference.

[0101] In addition, according to another exemplary embodiment of the present invention, there is provided a method for manufacturing an electrode assembly, the manufacturing method comprising the following steps:

[0102] (a) preparing an electrode and a counter electrode, wherein the electrode has the following structure: an electrode active material layer is formed on an electrode current collector, the electrode current collector comprising an electrode current collecting substrate and a tab extending from the electrode current collecting substrate;

[0103] (b) preparing a laminate by coating an organic-inorganic hybrid composition including inorganic particles and a binder polymer on a release film and drying the composition to thereby laminate an organic-inorganic hybrid film on the release film;

[0104] (c) forming an insulating film on a part or the whole of at least one surface of the joint of the electrode by laminating an organic-inorganic hybrid film after removing a release film from the laminate or directly transferring the organic-inorganic hybrid film from the laminate; and

[0105] (d) manufacturing an electrode assembly having a separator interposed between an electrode having an insulating film formed on at least one surface of a joint and an opposite electrode.

[0106] The electrode and the counter electrode in step (a) can be prepared in the same structure as described above.

[0107] The formation of the laminate in step (b) is performed by coating the organic-inorganic hybrid composition on the release film and drying it. At this time, the coating thickness of the organic-inorganic hybrid composition can be formed to correspond to the thickness of the above-mentioned insulating film, and drying can be performed at 60° C. to 120° C. for 5 to 10 minutes to evaporate the solvent used when preparing the organic-inorganic hybrid composition.

[0108] The preparation of the organic-inorganic hybrid composition is similar to that of the organic / inorganic composite porous coating of the SRS separator, and reference is made to these contents.

[0109] The lamination in step (c) refers to a method of first removing the organic-inorganic hybrid film from the release film and then laminating the removed organic-inorganic hybrid film alone on the electrode. At this time, lamination can be performed by a method such as pressing or bonding.

[0110] The transfer in step (c) refers to a process in which only the organic-inorganic hybrid film is directly transferred from the release film formed with the organic-inorganic hybrid film to at least one side of the joint. This transfer method can be performed by rolling transfer and heat transfer, and for example, the transfer can be performed by laminating the organic-inorganic hybrid film of the laminate to face the joint of the electrode, and then transferring the organic-inorganic hybrid film from the laminate to the joint of the electrode by rolling or heating.

[0111] In addition, as described above, such an insulating film may be formed on the joint of the electrode in the direction in which the electrode and the counter electrode face each other, and may even further be formed on the joint of the counter electrode in the direction in which the electrode and the counter electrode face each other.

[0112] Step (d) is the same as the general method for manufacturing an electrode assembly known in the art.

[0113] In addition, according to yet another exemplary embodiment, a lithium secondary battery including an electrode assembly and an electrolyte is provided.

[0114] The electrolyte generally uses a non-aqueous electrolyte containing lithium salt and is composed of a non-aqueous electrolyte and a lithium salt. The non-aqueous electrolyte uses a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc., but is not limited thereto.

[0115] The non-aqueous organic solvent may be an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethyl ether, methyl propionate, ethyl propionate, and the like.

[0116] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, poly(l-lysine), polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, ionomer-containing polymers, etc. can be used.

[0117] The inorganic solid electrolyte can use, for example, Li nitrides, halides and sulfates, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, etc.

[0118] Lithium salt is a material that can be well dissolved in non-aqueous electrolytes, such as LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, low-fat lithium carbonate, 4-phenylborate lithium, imide, etc.

[0119] In addition, in order to improve the charge and discharge characteristics, flame retardancy, etc., the non-aqueous electrolyte may also be added with, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolinidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, trichloroaluminum, etc. In some cases, the non-aqueous electrolyte may also include a halogen-containing solvent such as carbon tetrachloride, trifluoroethylene, etc. to impart non-flammability, and also include carbon dioxide gas to improve high temperature storage characteristics, and also include fluoroethylene carbonate (FEC), propylene sultone (PRS), etc.

[0120] As described above, such a lithium secondary battery according to the present invention may be a lithium ion battery, a lithium polymer battery, a lithium metal battery, and a lithium-free battery.

[0121] Such a lithium secondary battery can be used as a power source for a device, such as, but not limited to, a laptop, a netbook, a tablet computer, a mobile phone, an MP3, a wearable electronic device, a power tool, an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), an electric bicycle, an electric scooter, an electric golf cart, or a power storage system.

[0122] Hereinafter, the present invention will be described with reference to examples, but these examples are for easier understanding of the present invention, and the scope of the present invention is not limited thereto.

[0123] <Preparation Example 1> (Organic layer)

[0124] A polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVdF-CTFE) polymer was added to acetone at about 5 weight percent and then dissolved at a temperature of 50° C. for about 12 hours to prepare a polymer solution.

[0125] <Preparation Example 2> (Organic-inorganic hybrid layer: for coating)

[0126] BaTiO3 powder was added to the polymer solution of Preparation Example 1 so that the ratio was BaTiO3 / PVdF-CTFE=90 / 10 (ratio in weight percentage), and crushed and pulverized for 12 hours or more by using a ball milling method to prepare an organic-inorganic hybrid composition. The particle size of BaTiO3 can be controlled according to the size (particle size) of beads used in the ball milling method and the application time of the ball milling method, but in Preparation Example 2, the particle size of BaTiO3 was pulverized to about 400nm to prepare an organic-inorganic hybrid composition.

[0127] <Preparation Example 3> (Organic-inorganic hybrid film: for insulating film)

[0128] The organic-inorganic hybrid composition prepared in Preparation Example 2 was coated on a PET release film in a thickness of 10 μm and dried to prepare a laminate having an organic-inorganic hybrid film formed on the release film.

[0129] <Preparation Example 4> (Preparation of SRS Separator)

[0130] A polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVdF-CTFE) polymer is added to acetone at about 5 weight percent and then dissolved at a temperature of 50°C for about 12 hours to prepare a polymer solution. BaTiO3 powder is added to the polymer solution at a ratio of BaTiO3 / PVdF-CTFE=90 / 10 (ratio of weight percent), and is crushed and pulverized for 12 hours or more by using a ball milling method to prepare a slurry. The particle size of BaTiO3 in the slurry prepared above can be controlled according to the size (particle size) of the beads used in the ball milling method and the application time of the ball milling method, but in Preparation Example 4, the particle size of BaTiO3 is pulverized to about 400nm to prepare the slurry. The slurry prepared above is coated on a polyethylene diaphragm (porosity of 45%) with a thickness of about 18μm by using a dip coating method so that the coating thickness is adjusted to about 3.5μm. The coated polyethylene separator was dried at 60° C. to form an active layer, and as a result of measuring the active layer using a porosimeter, the pore size and porosity of the active layer coated on the polyethylene separator were 0.5 μm and 58%, respectively.

[0131] <Example 1>

[0132] The positive electrode active material (LiNi 0.6 Co 0.2 Mn 0.2 A positive electrode mixture consisting of 200 wt % O2, 2.5 wt % Super-P (conductive material) and 2.5 wt % PVDF (binder) was added to the solvent NMP (N-methyl-2-pyrrolidone) to prepare a positive electrode slurry. After that, the positive electrode slurry was coated (100 μm) on an aluminum current collector, and an aluminum tab was welded on the uncoated portion of the current collector to prepare a positive electrode.

[0133] The negative electrode was prepared by roll-transferring 40 μm of lithium metal onto a copper current collector and welding a copper tab on the uncoated portion of the current collector.

[0134] The positive electrode was prepared so that the portion excluding the joint had a size of 3.0 cm × 4.5 cm, and the negative electrode was prepared so that the portion excluding the joint had a size of 3.1 cm × 4.6 cm. Then, the organic-inorganic hybrid film was transferred from the side where the positive electrode and the negative electrode faced each other to the entire joint portion of the positive electrode using the laminate of Preparation Example 3 to form an insulating film.

[0135] The transfer was performed by laminating the laminate on the tab portion of the positive electrode to face the organic-inorganic hybrid film and then rolling the laminate with a roller.

[0136] The SRS separator obtained in Preparation Example 4 was inserted between the positive electrode and the negative electrode to prepare an electrode assembly (double cell). The electrode assembly was placed in a bag-shaped case and connected to an electrode lead, and then a dimethyl carbonate (DMC) solution in which 4M LiTFSI salt was dissolved was injected and sealed to assemble a lithium secondary battery.

[0137] <Example 2>

[0138] In Example 2, the positive electrode was prepared so that the size of the portion excluding the joint was 3.1 cm×4.6 cm, and the negative electrode was prepared so that the size of the portion excluding the joint was 3.0 cm×4.5 cm. Then, the organic-inorganic hybrid film was transferred from the side where the positive electrode and the negative electrode faced each other to the entire joint portion of the negative electrode using the laminate of Preparation Example 3 to form an insulating film.

[0139] <Comparative Example 1>

[0140] In Comparative Example 1, a lithium secondary battery was assembled in the same manner as in Example 1, except that any insulating film was not formed on the negative electrode and the positive electrode.

[0141] <Comparative Example 2>

[0142] In Comparative Example 2, a lithium secondary battery was assembled in the same manner as in Example 1, except that the organic-inorganic hybrid composition of Preparation Example 2 was coated on the entire joint portion of the positive electrode in a thickness of 10 μm without using the laminate of Preparation Example 3 and dried at 60° C. to form an insulating film.

[0143] <Comparative Example 3>

[0144] In Comparative Example 3, a lithium secondary battery was assembled in the same manner as in Example 1, except that the polymer solution prepared in Preparation Example 1 was coated on the entire tab portion of the positive electrode in a thickness of 10 μm without using the laminate of Preparation Example 3 and dried at 60° C. to form an insulating film.

[0145] <Comparative Example 4>

[0146] In Comparative Example 4, a lithium secondary battery was assembled in the same manner as in Example 1 except that an insulating tape (made of PET, 3M, thickness: 30 μm) was attached to the entire joint portion of the positive electrode without forming insulating films on the negative and positive electrodes.

[0147] <Experimental Example 1> Short Circuit Occurrence Rate Experiment

[0148] In order to determine the safety of the lithium secondary batteries manufactured in Examples 1 to 2 and Comparative Examples 1 to 4, while performing life evaluation at room temperature (25° C.), it was confirmed that a voltage drop phenomenon occurring when a short circuit occurs occurs before 200 cycles.

[0149] The lifetime was evaluated by charging and discharging at 1.0C for 200 cycles between 2.5V and 4.35V.

[0150] The results are shown in Table 1 below.

[0151] (Table 1)

[0152]

[0153] Referring to Table 1, in Comparative Example 2 in which the insulating layer was not formed at all, a short circuit occurred even before 200 cycles, whereas when the insulating layer was formed, it was confirmed that no short circuit occurred.

[0154] <Experimental Example 2> Defect Rate Experiment

[0155] 100 lithium secondary batteries prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were prepared, and the 100 lithium secondary batteries were charged and discharged 3 times at 0.1C in the range of 2.5V to 4.5V, and the number of cells whose capacity decreased from the first to the third measurement was shown in Table 2 below.

[0156] (Table 2)

[0157]

[0158] Referring to Table 2, it can be seen that in the case of using the insulating film according to the present invention, capacity reduction did not occur, while in the case of coating the organic layer, coating the organic / inorganic layer, and coating the insulating tape, capacity was reduced.

[0159] In the case of coating an organic layer or an organic / inorganic layer, the insulating tape of Comparative Example 4 had no ion conductivity since the coating material filled the pores on the electrode layer during the coating process, and thus exhibited no capacity at all in the covered portion.

[0160] <Experimental Example 3> Experiment on improving thermal explosion by endothermic effect of inorganic materials

[0161] In order to confirm the improvement of the safety of the lithium secondary batteries prepared in Experimental Examples 1 to 2 and Comparative Examples 1 to 4, the prepared batteries were subjected to a hot box test while the temperature was increased from 130° C. at a rate of 5° C. / min for 1 h, and the results are shown in Table 3.

[0162] (Table 3)

[0163] Explosion temperature(℃) Example 1 181 Example 2 180 Comparative Example 1 172 Comparative Example 2 180 Comparative Example 3 172 Comparative Example 4 173

[0164] Referring to Table 3, it can be seen that in Comparative Examples 3 to 4 containing no inorganic particles and Comparative Example 1 containing no insulating layer, the explosion temperature is relatively low.

[0165] While the invention has been described in conjunction with what are presently considered to be practical exemplary embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0166] Industrial Applicability

[0167] As described above, in the electrode assembly according to the present invention, an insulating film is formed on part or all of at least one side of the joint of the electrode to prevent short circuits between the electrodes due to internal / external short circuits, local crushing, etc. In addition, the insulating film is configured as an organic-inorganic hybrid film having ion conductivity, thereby preventing resistance from increasing even if the insulating film is partially formed on the electrode active material layer.

[0168] Furthermore, a separate insulating film is formed rather than in a coated form to prevent performance degradation of the secondary battery, such as resistance increase, capacity decrease, etc., which may be manifested by impregnation of the coating material into pores on the surface of the electrode active material layer.

[0169] Furthermore, the insulating film includes a specific organic material to delay thermal explosion due to the heat absorption effect of the inorganic material.

Claims

1. An electrode assembly for a lithium secondary battery, the electrode assembly comprising: electrodes, separators and counter electrodes, The electrode comprises an electrode current collector and a joint, and the electrode current collector comprises an electrode active material layer. an insulating film is formed on some or all of at least one surface of the joint, and the insulating film is an organic-inorganic hybrid film including inorganic particles and a binder polymer, The insulating film is formed on both sides of the joint of the electrode so as not to interfere with the migration of lithium ions when the electrode is charged and discharged.

2. The electrode assembly according to claim 1, wherein: The insulating film is further formed on a joint of the opposite electrode in a direction in which the electrode and the opposite electrode face each other.

3. The electrode assembly according to claim 1, wherein: The binder polymer is at least one selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose and polyvinyl alcohol.

4. The electrode assembly according to claim 1, wherein: The inorganic particles are at least one selected from the group consisting of (a) inorganic particles having a dielectric constant of 1 or more, (b) inorganic particles having piezoelectricity, (c) thermally conductive inorganic particles, and (d) inorganic particles having lithium ion transporting capability.

5. The electrode assembly according to claim 1, wherein: The content of the inorganic particles is 1 to 99 weight percent per 100 weight percent of a mixture of the inorganic particles and the binder polymer.

6. The electrode assembly according to claim 1, wherein: The insulating film is formed to have a thickness of 0.1 μm to 100 μm.

7. The electrode assembly according to claim 1, wherein: The electrode is a positive electrode and the counter electrode is a negative electrode.

8. The electrode assembly according to claim 1, wherein: The electrode is a cathode and the counter electrode is a cathode.

9. The electrode assembly according to claim 1, wherein: The diaphragm is a safety-enhanced diaphragm.

10. A method for manufacturing an electrode assembly, the method comprising the following steps: (a) preparing an electrode and a counter electrode, wherein the electrode has a connector; (b) preparing a laminate by coating an organic-inorganic hybrid composition including inorganic particles and a binder polymer on a release film and drying the composition to thereby laminate an organic-inorganic hybrid film on the release film; (c) forming an insulating film on some or all of at least one surface of the joint of the electrode by laminating the organic-inorganic hybrid film after removing the release film from the laminate or directly transferring the organic-inorganic hybrid film from the laminate; as well as (d) manufacturing the electrode assembly with a separator interposed between the electrode and the counter electrode on which the insulating film is formed on at least one surface of the joint, Wherein, the electrode assembly for a lithium secondary battery comprises: electrodes, separators and counter electrodes, The electrode comprises an electrode current collector and a joint, and the electrode current collector comprises an electrode active material layer. An insulating film is formed on some or all of at least one surface of the joint, and the insulating film is an organic-inorganic hybrid film including inorganic particles and a binder polymer, and The insulating film is formed on both sides of the joint of the electrode so as not to interfere with the migration of lithium ions when the electrode is charged and discharged. 11 . A lithium secondary battery, comprising the electrode assembly according to claim 1 .

Citation Information

Patent Citations

  • Mold for headliner of vehicle

    KR1020200024624A